2005
DOI: 10.1007/s10800-004-6202-z
|View full text |Cite
|
Sign up to set email alerts
|

Zeolite-based composite membranes for high temperature direct methanol fuel cells

Abstract: Composite Nafion membranes containing three natural zeolites (Mordenite, Chabazite and Clinoptilolite) were prepared by using a recast procedure for application in high temperature Direct Methanol Fuel Cells (DMFCs). The Nafion-zeolite membranes have shown good properties for high temperature DMFC application, due to their improved water retention characteristics. A maximum power density of 390 mW cm )2 was achieved at 140°C with the mordenite-based composite membranes in the presence of oxygen feed. The elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 17 publications
1
39
0
Order By: Relevance
“…Many researchers have selected inorganic materials to improve the water retention in the membrane and also to decrease the alcohol crossover [12][13][14][15]. Zeolite is a well-defined microporous structure of crystalline aluminosilicates containing silicon and oxygen in its framework.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have selected inorganic materials to improve the water retention in the membrane and also to decrease the alcohol crossover [12][13][14][15]. Zeolite is a well-defined microporous structure of crystalline aluminosilicates containing silicon and oxygen in its framework.…”
Section: Introductionmentioning
confidence: 99%
“…They are hydrophilic substances with molecular sieve properties [5,12], preferring to adsorb water to alcohol and providing a good proton pathway through the membrane while blocking the diffusion path of alcohol inside a Nafion composite membrane. In addition, mordenite and analcime are stable in acid and have high temperature tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Several works have been reported on Nafion-zeolite composite membranes, including reports on the incorporation of acid functionalized zeolites to improve the proton conductivity of the composite membrane [25,[30][31][32] or to improve the dispersion of the zeolite particles, and studies on the effect of the zeolite particle size, the Si/Al ratio [33], or the solvent used in membrane fabrication. Some of these studies confirmed that zeolites can improve the performance of Nafion based DMFCs operating at temperature higher than 70 • C and with O 2 fed at the cathode, although the impact of the zeolite incorporation on the proton conductivity and methanol permeability of membranes varies between the reported works.…”
Section: Introductionmentioning
confidence: 99%
“…65 summarized the materials which commonly used in DAFC membrane, which are the Nafion from Dupont, Sulfonated Poly ether ether ketone (SPEEK), and polyvinyl acetate (PVA). A lot of researchers [69][70][71][72][73][74][75][76][77][78][79][80] developed composites based on those materials to improve the efficiency of the DAFC. The development occurred in both PEM and AEM.…”
Section: Membrane In Direct Alcohol Fuel Cellsmentioning
confidence: 99%
“…The zeolite itself has a similarity to other PEM materials which makes it suitable for a DAFC. The zeolite membrane may appear in the form of pure zeolite itself, 68 as a composite with mentioned materials 73,75,76,[81][82][83] or as a composite form with other new materials. 84 Compared to the existing membrane materials, the zeolite composite membranes give improved performance in term of proton conductivity and alcohol crossover.…”
Section: Zeolite In Direct Alcohol Fuel Cellsmentioning
confidence: 99%